2010
DOI: 10.1111/j.1745-5871.2009.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

People, Space and Place: a Multidimensional Analysis of Unemployment in Metropolitan Labour Markets

Abstract: It is becoming increasingly apparent that, in order to understand a range of socio-economic outcomes, research needs to be focused on a multi-dimensional approach that accounts for individual characteristics and behaviours together with locality and activity within space and place. Within labour market analysis there is a need to situate empirical analysis within a conceptual framework that considers both the assets of individuals within the labour force and the social and local labour market contexts in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Van Bueren, Klijn, & Koppenjan, 2003;Klijn & Koppenjan, 2004;Ansell & Gash, 2008). In addition, scholars are enabled to tie scholarly debates to contemporary societal issues, such as unemployment (Baum & Mitchell, 2010), health care (e.g. Ferlie, Fitzgerald, McGivern, Dopson, & Bennet, 2011), mental health (Hannigan & Coffey, 2011), education (Bore & Wright, 2009), environment, energy and health (Turnpenny, Lorenzoni, & Jones, 2009).…”
Section: The Three Tenets Of Wickedness Theorymentioning
confidence: 99%
“…Van Bueren, Klijn, & Koppenjan, 2003;Klijn & Koppenjan, 2004;Ansell & Gash, 2008). In addition, scholars are enabled to tie scholarly debates to contemporary societal issues, such as unemployment (Baum & Mitchell, 2010), health care (e.g. Ferlie, Fitzgerald, McGivern, Dopson, & Bennet, 2011), mental health (Hannigan & Coffey, 2011), education (Bore & Wright, 2009), environment, energy and health (Turnpenny, Lorenzoni, & Jones, 2009).…”
Section: The Three Tenets Of Wickedness Theorymentioning
confidence: 99%
“…Little account is taken of the social impacts of urban consolidation (Randolph, 2002;Randolph et al, 2010). While there is an acknowledgement of the different kinds of economic and social circumstances in different parts of the metropolitan areas, as in Western Sydney (SGS Economics & Planning, 2004), the metropolitan strategy addresses these in land use terms and dwelling and workforce targets parcelled up into arbitrary regions without recognition of the complex interplay of labour and housing markets which these circumstances reflect (Baum et al, 2006;Baum, 2007). Studies of Western Sydney have shown the finegrained nature of these conditions of social disadvantage and lack of employment opportunities (Fagan & Dowling, 2005).…”
Section: Social and Economic Developmentmentioning
confidence: 98%
“…Second, it enables scholars to tie these insights to contemporary, urgent societal matters, such as unemployment (Baum and Mitchell 2010), health care (e.g. Ferlie et al, 2011), mental health (Hannigan and Coffey, 2011), education (Bore and Wright, 2009), environment, energy and health (Turnpenny et al, 2009).…”
Section: Defining Transboundary Wickednessmentioning
confidence: 99%